Paravian Phylogeny and the Dinosaur-Bird Transition: An Overview - Agnolin, Federico L.; Motta, Matias J.; Brissón Egli, Federico; Lo Coco, Gastón; Novas, Fernando E. (Frontiers in Earth Science, 2019)
Recent years witnessed the discovery of a great diversity of early birds as well as closely related non-avian theropods, which modified previous conceptions about the origin of birds and their flight. We here present a review of currently the taxonomic composition and main anatomical characteristics of those theropod families closely related with early birds, with the aim to analyze and discuss main phylogenetic hypotheses that compete some topics about the non-avian dinosaur-bird transition. We conclude that troodontid affinities of anchiornithines, and dromaeosaurids affinities of microraptorians and unenlagiids are dismissed in favor of sister group relationships with Avialae. After recodification of unenlagiids the topology of the TWiG phylogenetic scheme, results on a large polytomy at the base of Pennaraptora. Regarding character evolution, we found that: 1) presence of ossified sternum goes hand by hand with the presence of ossified uncinate processes; 2) presence of folded forelimbs in basal archosaurs indicates a widespread distribution among reptiles, contradicting previous proposals in that forelimb folding driven by propatagial and associated tendons was exclusive of the avian lineage; 3) in basal paravians and avialans as Archaeopteryx the wings are relatively large and wide, with relatively short rectricial feathers, and rounded alar contour, having a convex wing attack margin. These taxa exhibit restricted folding capabilities of forelimbs, preserving hands with flexor angles (respect to radius/ulna) no lesser than 90º. In more derived birds, instead, rectrices are notably elongate and the angle described between the hand and forearm is much less than 90º, indicating not only an increased folding capability of the forelimbs, but also increased variety of beat movements of the wing during flight. Because of the strong similarities on pectoral girdle conformation between ratites and basal avialans and paravians, it is possible to infer that main forelimb movements were similar in all these taxa, lacking the complex dorsoventral wing excursion characteristic of living neognathans.